2014
DOI: 10.1038/sj.bdj.2014.884
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in unstimulated salivary flow rate in burning mouth syndrome

Abstract: BMS patients have statistically significant decreased unstimulated salivary flow rate with non-statistically significant decreased stimulated flow rate. Salivary flow rates in BMS patients are decreased further by medication usage whose side effects include dry mouth. This suggests that hyposalivation may play a role in causing dry mouth in BMS, which may respond to treatment with a sialogogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 18 publications
3
37
3
3
Order By: Relevance
“…Although many BMS patients complain the feeling of dry mouth, most of the studies have shown that the salivary flow rate in BMS patients is the same as in controls (Hershkovich and Nagler, 2004;Granot and Nagler, 2005;de Moura et al, 2007). However, recently, in contrast to Boras et al (2010), Lee et al (2015) and Poon et al (2014) reported decreased unstimulated salivary flow rates in primary BMS patients compared to those of healthy controls, however, without any differences in stimulated salivary flow rates.…”
Section: Hyposalivation and Xerostomiamentioning
confidence: 95%
“…Although many BMS patients complain the feeling of dry mouth, most of the studies have shown that the salivary flow rate in BMS patients is the same as in controls (Hershkovich and Nagler, 2004;Granot and Nagler, 2005;de Moura et al, 2007). However, recently, in contrast to Boras et al (2010), Lee et al (2015) and Poon et al (2014) reported decreased unstimulated salivary flow rates in primary BMS patients compared to those of healthy controls, however, without any differences in stimulated salivary flow rates.…”
Section: Hyposalivation and Xerostomiamentioning
confidence: 95%
“…The affected patients are mostly peri-or postmenopausal women, and there is a clear association with psychological comorbidities. Interestingly, the unstimulated salivary flow rate has been found to be lower in patients with BMS [89][90][91][92].…”
Section: Burning Mouth Syndromementioning
confidence: 99%
“…Mental stress and menopause suppress salivary secretion, especially unstimulated flow rate. Some studies indicated that unstimulated salivary flow rate was significantly lower in BMS patients than in controls, despite the absence of a significant difference in stimulated flow rate . Minor salivary glands are important in oral tissue lubrication, and oral dryness in resting state is considerable because of decreased secretion by minor salivary glands .…”
Section: Introductionmentioning
confidence: 99%